Tourism under the national development plan in Malaysia / Dr. Muhammad Hanif Othman and Zouhair Mohd Rosli - Othman, Muhammad Hanif; Mohd Ros, Zouhair (Universiti Teknologi MARA, Kedah, 2022)
The tourism sector in Malaysia plays a pivotal role in fostering the country's overall economic growth and inclusivity. Such significance is evident through its incorporation into various national plans aimed at advancing human capital development and improving the socioeconomic landscape. Development plans for tourism began with the First Malaysia Plan in 1966-1970, where the government provided incentives for hotel construction and upgrades. A more defined roadmap for tourism unfolded during the Second Malaysia Plan (1971-1975), which targeted 170,000 tourist arrivals by air and sea in 1975. This represented an average annual growth of 17%, surpassing the 13.7% recorded during the First Malaysia Plan (Economic Planning Unit, 1971). During the Second Malaysia Plan (1971-1975), employment in the tourism sector was more than doubled from 5,200 in 1970 to 13,870 in 1974. The Bumiputera's participation in the sector also doubled, with their ownership of hotels and motels increasing from 14 in 1972 to 28 in 1975, involving a capital outlay of USD 24.6 million (Economic Planning Unit, 1976). Additionally, the number of Malay-owned travel and tour agencies rose from 42 to 115. Out of 100 licenses issued for tourism agency operation, 46 were allocated to the Bumiputera. The tourism development, which created employment opportunities and benefited targeted groups such as Bumiputera, served the principles of the then main development plan, namely the New Economic Policy (NEP). NEP aimed to enhance the well-being of low-income households and promote economic participation across different ethnic groups, particularly the Bumiputera community (Marzuki, 2010). Subsequent plans for the tourism sector have also been continuously outlined in various development frameworks, including the New Economic Model (NEM) (2011-2020) and the Shared Prosperity Vision (SPV) 2030 (2021- 2030). The emphasis on tourism development continued in the Eleventh Malaysia Plan (2016- 2020) under Strategy Paper 18C focusing on transforming the services sector into a modern, knowledge-intensive industry (Economic Planning Unit, 2015a). The plan highlighted key areas such as knowledge-intensive sectors and the creation of high-income jobs within the tourism sector. Tourism held a significant role as a high-impact project in the Eleventh Malaysia Plan under the Regional Economic Corridors Development (Economic Planning Unit, 2015b). The target was to generate RM103.9 billion of Gross National Income (GNI), bringing in approximately RM168 billion in tourist receipts and accommodating 36 million arrivals by 2020 (Performance Management & Delivery Unit, 2013; Tourism Malaysia, 2018). Similarly, the Twelfth Malaysia Plan (2021-2025) stressed the importance of tourism as a high-potential growth industry to elevate the country along the value chain. Considering the prolonged challenge of low value-added issues, tourism emerged as a key player in enhancing productivity through higher value-added and knowledge-intensive activities (Economic Planning Unit, 2021). Considering the impacts of the COVID-19 pandemic, the targets set during the Twelfth Malaysia Plan (2021-2025) period are more conservative than